Pre-analytical, analytical, and post-analytical considerations while processing samples of COVID-19 patients: Perspective from a clinical chemistry laboratory in India - Das, Saswati; Koner, Bidhan Chandra (Asian Journal of Medical Sciences, 2020)
Background: Since its detection in December 2019 in the city of Wuhan, China, the COVID-19 pandemic has grappled the world. Laboratories have been central in the diagnosis, prognosis and therapeutic monitoring of COVID-19 patients. With this pandemic spreading, laboratory personnel have become vital in the efforts to halt the advance of the virus. Aims and Objective: In this article, we will address various concerns in all the three phases of testing of the COVID-19 blood and serum samples in a clinical chemistry laboratory and discuss the issues pertaining to a resource-limited setting. Materials and Methods: International, national and regional guidelines on bio-safety and operational management available at the time of preparation of this manuscript were analyzed. Additionally, literature search through PubMed was done on the keywords “bio-safety”, “pre-analytical”, “analytical”, “post-analytical” and “COVID-19”. Results: The pre-analytical, analytical, post analytical, general management problems we faced in our laboratory and the best practices that we followed to address the same has been included in this paper. Conclusion: Some unprecedented challenges the laboratories have encountered during this outbreak are maintaining the lab safety of highest standards, management of human resource while sustaining the quality of testing. Laboratories will have to constantly innovate in order to meet the demands of this outbreak.